The Political Impact of the Sustainable Development Goals Transforming Governance Through Global Goals? - Biermann, Frank; Hickmann, Thomas; Sénit, Carole-Anne (Physical Sciences, 2022)
The first comprehensive global assessment of the political impact of the Sustainable Development Goals that the United Nations launched in 2015. Written by a team of over sixty experts and drawing on over 3000 scientific studies, this volume is a key resource for policymakers, activists and scholars of sustainable development.